2010
DOI: 10.1007/s12600-010-0113-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different temperatures and relative humidity on the development, mortality and nymphal predation of Anthocoris minki

Abstract: Mass rearing techniques are a necessity in developing a suitable and economic biological control method. Anthocoris minki Dohrn (Heteroptera: Anthocoridae), which is successfully reared for use in biological control, is a promising indigenous Anthocoris species for biological control of Agonoscena pistaciae Burckhardt and Lauterer (Homoptera: Psyllidae) in pistachio orchards. Development time of nymphal instars, mortality percentage and prey consumption of A. minki fed on Ephestia kuehniella Zeller (Lepidopter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Knowing how much food is consumed is an important parameter in the mass rearing of predators. E. kuehniella egg consumption of immature stages of A. minki at 40 and 65% RH was recorded by Yanik and Unlu (2010) The intrinsic rate of natural increase is the most decisive data for estimating population dynamics (Southwood 1978). In this study, the highest r m (0.112) was observed at 30°C and 65% RH.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Knowing how much food is consumed is an important parameter in the mass rearing of predators. E. kuehniella egg consumption of immature stages of A. minki at 40 and 65% RH was recorded by Yanik and Unlu (2010) The intrinsic rate of natural increase is the most decisive data for estimating population dynamics (Southwood 1978). In this study, the highest r m (0.112) was observed at 30°C and 65% RH.…”
Section: Discussionmentioning
confidence: 54%
“…The sex ratio of progeny from the stock culture of the predator was found to be 1:1. The developmental time (from egg to adult stage) was measured for each temperature and RH in a previous study (Table 1) (Yanik and Unlu 2010).…”
Section: Laboratory Rearing Of a Minkimentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of insecticide failure, biological controls are gaining prominence for controlling pistachio psylla. In Turkey, Anthocoris minki Dohrn (Hemiptera: Anthocoridae) has an important role as a natural enemy of pistachio psylla (Çelik, 1981;Mart et al, 1995;Yanik & Unlu, 2010). Based on data obtained from insect release studies in pistachio orchards, Yanık et al (2007) reported that A. minki was effective for controlling pistachio psylla and was responsible for decreasing the pest population at the economic injury level.…”
Section: Introductionmentioning
confidence: 99%
“…Based on data obtained from insect release studies in pistachio orchards, Yanık et al (2007) reported that A. minki was effective for controlling pistachio psylla and was responsible for decreasing the pest population at the economic injury level. Detailed studies regarding the biology, ecology, and release of A. minki for controlling pistachio psylla are available in the scientific literature (Yanik & Unlu, 2010;2011a, b;Yanık et al, 2007;2011a, b;.…”
Section: Introductionmentioning
confidence: 99%